Polarization and Accountability in Covid Times - Beramendi, Pablo; Rodden, Jonathan (Frontiers in Political Science, 2022)
We analyze the relationship between accountability and polarization in the context of the COVID crisis. We make three points. First, when voters perceive the out-party to be ideologically extreme, they are less likely to hold incumbents accountable for poor outcomes via competence-based evaluations. Knowing this, even in the context of major crises, incumbents face weaker incentives to take politically costly measures that would minimize deaths. Second, there is a partisan asymmetry whereby the additional government intrusion associated with effective COVID response can be more politically costly for the right than for the left, because it undercuts the ideological distinctiveness that drives the base-mobilization strategy of the right. Third, this asymmetry generates incentives for politicization of COVID mitigation policies that ultimately lead to partisan differences in mitigation behavior and outcomes. To illustrate this logic, we provide preliminary evidence that COVID death rates are higher in more polarized democracies, and that in one of the most polarized democracies—the United States—COVID deaths have become increasingly correlated with partisanship.